1959
DOI: 10.1002/ange.19590710503
|View full text |Cite
|
Sign up to set email alerts
|

Katalytische Umsetzungen von Olefinen an Platinmetall‐Verbindungen Das Consortium‐Verfahren zur Herstellung von Acetaldehyd

Abstract: ungeheuren Reaktionsfahigkeit nicht zusammen bestehen konnen. Deshalb darf man nicht erwarten, auf der Erde betrachtliche Mengen oder sogar komplizierte einzelne Atome von Antimaterie finden zukonnen.Sehr einfache Kerne, wie z. B. Antideuteronen werden vielleicht mit Beschleunigern gro6erer Energie als wir sie heute haben, dargestellt werden konnen. Aber eine irdische Antichemie scheint mir zu viel, sogar fur die Zukunft.Man stellt sich dann natiirlich die Frage, ob es nicht vielleicht im Kosmos gro6e Meiigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
227
0
19

Year Published

1970
1970
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 664 publications
(247 citation statements)
references
References 7 publications
1
227
0
19
Order By: Relevance
“…4, 5). These induction periods are consistent with the work reported by Smidt et al (1,20) who demonstrated that the uptake of internal and branched olefins by Pd(I1) salts is significantly slower than that of terminal olefins.…”
Section: Fig 3 Current (--)supporting
confidence: 92%
See 1 more Smart Citation
“…4, 5). These induction periods are consistent with the work reported by Smidt et al (1,20) who demonstrated that the uptake of internal and branched olefins by Pd(I1) salts is significantly slower than that of terminal olefins.…”
Section: Fig 3 Current (--)supporting
confidence: 92%
“…The rate of ligand exchange is acid catalysed at low acid concentration but approaches a limiting value at high acid concentration (17). Alternatively, the acceleration by low concentrations of acid may be a result of protonation of the ligand, which would increase the electrophilicity of the Pd(I1) and increase its reactivity towards the olefin (18)(19)(20). The inhibition at high…”
Section: Fig 2 Oxygenate Yield Versus [Hclo] For the Homogeneousmentioning
confidence: 99%
“…Analogous to the Wacker reaction over a homogeneous PdC1 2 catalyst [11,12], the first step (ethylene fi acetaldehyde) is assumed to involve redox of Pd between Pd 2+ and Pd 0 . In contrast, the second step (acetaldehyde oxidation) proceeds on the Pd metallic sites or the WO 3 sites in 1.0wt%Pd/W0 3 -ZrO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Invention of the Wacker process to produce acetaldehyde using PdCl 2 ±CuCl 2 as catalysts in 1959 is the ®rst example of the homogeneous palladium-catalyzed reaction [1]. Soon after the invention of the Wacker process, formation of vinyl acetate by the oxidative acetoxylation of ethylene with PdCl 2 in AcOH in the presence of NaOAc was reported by Moiseev [2].…”
Section: Introductionmentioning
confidence: 99%